A new flightless genus of Thaumastodinae from Australia (Coleoptera: Limnichidae) - Hernando, Carles (Zootaxa, 2023)
Austramastodus apterus gen. et sp. nov. from the Cape Range Peninsula, Australia (Western Australia) is described. This is the first Thaumastodinae recorded from continental Australia and the only terrestrial member of the subfamily not associated with any permanent aquatic habitat. It is probably closely related to Pseudeucinetus Heller, 1921, which is widespread in the Paleartic, Oriental and Australian regions. The new genus is apterous and characterized by the transverse head, widely separated eyes (space between them being larger than an eye diameter) and non-forwardly projecting frons. A key to all known genera of Thaumastodinae is provided.